VD_FINDINFO Jug / 2018 / 329 vom 9. Februar 2018 - VD Tribunal cantonal (2018)
CONSTATATION DES FAITS, TENTATIVEDROIT PÉNAL, MEURTRE, INTENTION, PARTIE CIVILE | 22 ad 111 CP, 47 CP, 10 CPP (CH), 425 CPP (CH)